2021
DOI: 10.7759/cureus.19723
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Impact of COVID-19 on Drug Store Management in a Tertiary Care Teaching Hospital of Central India

Abstract: Introduction: One-third of the annual hospital budget is spent on the purchase of medicines, materials, and supplies. Drug store management is a complex but critical process within the healthcare delivery system. Health supply chains, the import of active pharmaceutical ingredients, transportation, procurement, finished products have been disrupted by COVID-19. Materials & methods: A retrospective, observational study was carried out at the Department of Hospital Administration, All India Institute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Contrary to the consistent decrease in overall antibiotic consumption in the community, there was a different trend in antibiotic consumption in hospitals (13,14,(23)(24)(25)(26)(27)(28)). An increase was reported in hospitals in Spain, Italy, India, and the UK.…”
Section: Decrease/increase In Antibiotic Consumption In Hospitalsmentioning
confidence: 81%
See 3 more Smart Citations
“…Contrary to the consistent decrease in overall antibiotic consumption in the community, there was a different trend in antibiotic consumption in hospitals (13,14,(23)(24)(25)(26)(27)(28)). An increase was reported in hospitals in Spain, Italy, India, and the UK.…”
Section: Decrease/increase In Antibiotic Consumption In Hospitalsmentioning
confidence: 81%
“…Full text of remaining 66 articles were reviewed, and finally, 16 articles were included in this systematic review (13-28) (Figure 1). Eight studies reported only hospital-based results (13,14,(23)(24)(25)(26)(27)(28), nine reported only community-level antibiotic consumption (14-22), and one [conducted in England ( 14)] reported antibiotic consumption in both hospitals and communities (Tables 2, 3). Although we did not limit the studies to the year 2020, we could not find any study that reported antibiotic consumption in 2021 through the systematic review.…”
Section: Systematic Review Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, the Colombian Association of Intensive Care Medicine and the Colombian Society of Anesthesiology generated specific documents with recommendations for the sedation and analgesia approach in the context of the pandemic and drug shortages [15], which included the use of inhaled sedatives (a suggestion also reviewed by other authors [16,17]). The call for the rational use of pharmaceutical resources was widely described in the world, taking as example some publications in Singapore [18], the United States [19,20], India [21], and Italy [22]. Some limitations of this type of analysis are recognized, including that it did not consider variables related to drug consumption such as patient age, weight, and diagnosis, or the production and importation conditions according to the global demand for sedatives, opioids, and neuromuscular blockers.…”
Section: Discussionmentioning
confidence: 99%